Self-condemnation among the perpetrators of incest crimes - Obaid, Hijran Mohsen; Daghestani, Sana Issa (Al-Adab Journal, 2021)
The current research deals with the variable of the study, which is self-condemnation, which means a complex response with negative feelings stemming from severe reprimanding of the self for an unacceptable (rejected) behavior that violates laws, legislation and social norms, which leads to harm to others (the victim). It means ignoring the consequences of actions, when people continue to engage in harmful activities towards others to achieve personal gain, and in order to avoid facing the damages they have caused, they reduce the effects of these damages, especially if it is on the individual level to evade responsibility, and the issue of self-condemnation in the modern era has met the attention of researchers. Developed societies as one of the directions of psychology. In order to achieve the goals of the current research, the researcher adopted the theory of Woodyat & Wanzel (Woodyat & Wanzel, 2013) noting that it is a model developed from Hall and Fincham (Hall & Fincham, 2005). The paragraphs on the research scale according to the two methods (the two extremist groups and internal consistency) and the validity of the construct was extracted using the Pearson correlation coefficient, and the reliability coefficient for self-condemnation by the Alpha Cronbach method reached (0.85), and the current research sample consisted of (250) prisoners of the Iraqi Ministry of Justice, and they were all Of the males only, i.e. the one who is already present, distributed among eight prisons of the Ministry of Justice, they were selected randomly, and the research reached the following results: 1. That prisoners have self-conviction with statistical significance 2. There were no age differences in the variable of self-conviction. As for the achievement, there are differences in Achievement and in favor of the university level, and there were no statistically significant differences with regard to the economic level of the self-indictment variable, and the researcher suggested several proposals, including: 1. Conducting a study for self-condemnation with the variables of restorative behavior Pseudo-self-forgiveness 2. Conduct a study on incest with methods of parental treatment, family disintegration, and drug addiction.